Butyrophilins: γδ T Cell Receptor Ligands, Immunomodulators and More - Herrmann, Thomas; Karunakaran, Mohindar M. (Frontiers in Immunology, 2022)
Butyrophilins (BTN) are relatives of the B7 family (e.g., CD80, PD-L1). They fulfill a wide range of functions including immunomodulation and bind to various ligands such as the γδ T cell receptor (γδTCR) and small molecules. One intensively studied molecule is BTN3A1, which binds via its cytoplasmic B30.2 domain, metabolites of isoprenoid synthesis, designated as Phosphoantigen (PAg), The enrichment of PAgs in tumors or infected cells is sensed by Vγ9Vδ2 T cells, leading to the proliferation and execution of effector functions to remove the infected cells. This article discusses the contribution of BTNs, the related BTNL molecules and SKINT1 to the development, activation, and homeostasis of γδ T cells and their immunomodulatory potential, which makes them interesting targets for therapeutic intervention.